1998
DOI: 10.1063/1.120817
|View full text |Cite
|
Sign up to set email alerts
|

Charge release of lanthanum-doped lead zirconate titanate stannate antiferroelectric thin films

Abstract: The charge release speed and backward phase switching time of lanthanum-doped lead zirconate titanate stannate antiferroelectric thin films were investigated by directly measuring the switching current upon removal of the applied electric field. The backward switching time is about 6 ns. The maximum switching current density can reach 9400 A/cm2, and more than half of the stored charge can be released in 10 ns. These results show that the obtained antiferroelectric thin films are very promising for decoupling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(67 citation statements)
references
References 10 publications
3
61
0
Order By: Relevance
“…This characteristic of antiferroelectric ceramics makes them good candidates for high displacement electromehanical actuator applications [99][100][101][102][103]. In addition, the transformation of antiferroelectrics from AFE to FE phase leads to a significant energy storage, which can be used in energy storage applications [104,105]. Antiferroelectric ceramics are also studied because of their unique pyroelectric, electro-optical and many other useful properties [99].…”
Section: Antiferroelectricsmentioning
confidence: 98%
“…This characteristic of antiferroelectric ceramics makes them good candidates for high displacement electromehanical actuator applications [99][100][101][102][103]. In addition, the transformation of antiferroelectrics from AFE to FE phase leads to a significant energy storage, which can be used in energy storage applications [104,105]. Antiferroelectric ceramics are also studied because of their unique pyroelectric, electro-optical and many other useful properties [99].…”
Section: Antiferroelectricsmentioning
confidence: 98%
“…In the last two decades, doped lead zirconate titanate stannate antiferroelectric (AFE) materials have received increasing attention due to their larger electric-induced strain and unique double hysteresis loops, which have the potential usage in microelectric system, especially for higher energy storage applications and high-strain transducers/actuators [1,2]. Generally, most studies on the lead-contained AFE thin films were usually fabricated on Pt/Ti/SiO 2 /Si substrates directly.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding forwards phase transition has been investigated by Brooks et al 2 who reported switching within typically 300 ns. More recently, antiferroelectric thin films were also studied by Xu et al 3 using PbZrTiO 3 of about 0.4 m thickness, equally doped with lanthanum at the Aand with tin at the B-site of the perovskite structure, and deposited by a modified sol-gel method on conventional silicon substrates. Field forced FE-AFE backwards transition times below 10 ns were reported for these films.…”
Section: Introductionmentioning
confidence: 98%